DEALING WITH SPEAKING ANXIETY; A CASE STUDY OF THE IMPLEMENTATION OF SIDANG AKADEMI AT A SCHOOL IN CENTRAL JAVA - Purba, Hilarius Raditya Priambada; Setiawan, Slamet (LLT Journal: A Journal on Language and Language Teaching, 2021)
Speaking skill becomes a very important issue in second language acquisition. Among the four English skills being developed, speaking is crucial for students. Speaking anxiety is one of the burdens experienced by the students so that the exploration of the willingness to communicate is needed to maintain the problem. Moreover, in the Indonesian context, English is still a second/ foreign language so that when the student is required to speak in public using English the problem will be double. This research discussed the implementation of Sidang Akademi (Academic Preliminary Meeting) in a private Senior High School in Central Java as an obligatory activity for the students. This research employs a qualitative study specifically a case study. The result of the study presents that the implementation of the activity causes the student to experience speaking anxiety caused by many factors. There are also some ways in managing speaking performance conducted by the student in the implementation of the activity.